Validation of assisted forward osmosis (AFO) process : impact of hydraulic pressure - Blandin, Gaetan (2013)
The use of forward osmosis (FO) is of growing interest for water desalination, due to its potential energy savings. However, its industrial implementation is still limited by its actual performance limitation in water permeation and reverse salt diffusion, due to membrane properties. Assisted forward osmosis (AFO) is a new concept, aiming at pressurising the feed solution to enhance water permeation through synergising osmotic and hydraulic driving forces. This paper presents the impact of hydraulic pressure on the FO membrane properties and the overall performances of the system in order to validate the interest of AFO. When 6 bar was applied on the feed side of the process, the membrane water permeability (A) was observed to double, mainly due to the membrane deformation against the spacers. Under those conditions, the additional driving force provided resulted in 70% increase in permeation flux, despite the more severe concentration polarisation. More interestingly, the observed reverse salt diffusion was significantly lower than expected by the solution diffusion model, confirming the interest of AFO in tackling current limitations of FO technology. This study also revealed the relative limitations of the current methodology used for the determination of membrane solute and water permeabilities, which currently fail to consider membrane deformation that could arise in pressure retarded osmosis and AFO systems.